Campur Kode pada Lagu Pop Bali Karya Kroncong Jancuk : (Kajian Sosiolinguistik) - Ni Wayan Hari Santi Setya Negara; I Made Wiradnyana; I Made Luwih (Institut Nalanda, 2026)
Code-mixing is the use of more than one language in a single utterance to enrich the style or variety of language, whether in the form of words, clauses, or idioms. Code-mixing is commonly found in oral works in the form of songs, especially Balinese pop songs by Kroncong Jancuk. The problem formulations that will be discussed in this study are: 1) The forms of code-mixing found in songs by Kroncong Jancuk 2) The functions of code-mixing found in songs by Kroncong Jancuk 3) The impact of code-mixing found in songs by Kroncong Jancuk on the use of the Balinese language. The theories used to examine the above problems are code-mixing theory, borrowing typology theory, M.A.K. Halliday's language function theory, and Dell Hathaway Hymes' language choice theory. The data analysis used includes documentation and literature study with three stages, namely data reduction, presentation, and conclusion. The research results show that 1) the forms of code-mixing found in Kroncong Jancuk's Balinese pop songs include root words, affixed words, phrases, and clauses. 2) The functions of code-mixing in Kroncong's Balinese pop songs include ideational, interactional, imaginative, informative, and poetic functions. 3) The impacts found in Kroncong's Balinese pop songs include positive impacts such as maintaining the existence of the Balinese language in the modern era, clarifying meaning, and expanding listeners' understanding, as well as negative impacts such as the reduced use of the Balinese language in its entirety.